STRAWBERRY SORTING AND CLASSIFICATION SYSTEM TO INCREASE THE SELLING VALUE AND TO FACILITATE THE PACKING PROCESS USING ARTIFICIAL INTELLIGENCE - Hamdani, Dani; Heryono, Heri (International Journal of Psychosocial Rehabilitation, 2020)
Implementation and post-harvest sorting system are the most essential parts in agriculture and plantations; they lead to the quality and quantity maintenance of agricultural products. Some crops need to do grading and sorting techniques. Sorting functions to filter the type and quality of plants with a grading system and this method has also been carried out on potato, coffee and citrus plantations. In Indonesia, the sorting system is processed manually; so that the time process takes time and causes long queues when packaging. In consequence, the plantation products would be stored longer and it causes rotting process to the plantation products. In some developed countries, the sorting system is conducted with the computerized-system-assisted through the aid of optics or lenses stored on a conveyor machine. As the help of computer sorting equips with artificial intelligence methods; so that the computer is able to calculate and trade the types of plants. The results of plantations and even the system would be possibly able to recognize the types of diseases in plants. This AI technique has been applied in the sorting system of strawberry. The agricultural products of this fruit have a high selling value, the grading process is used to classify strawberry sizes in order to increase sales results with grading value parameters with Oblate, Globose, Conic, long Conic, and Conic. The parameters are assessed by size and whether there are defects in the fruit, so that the selling value is high, AI techniques has been proven to facilitate the process of sorting which capable of detailing each object's texture and more precision with an accuracy of 95%.